The tax treatment of haircuts in financial reorganizations - Aurelio GURREA-MARTINEZ (Institutional Knowledge at Singapore Management University, 2020)
Over the past few years, Singapore has implemented various ambitious insolvency reforms aimed at making the country an international hub for debt restructuring. This article argues that while Singapore has put in place one of the most sophisticated restructuring frameworks in the world, some tax reforms might be useful to maximise the potential of this new restructuring framework. Namely, it will be pointed out that the tax treatment of debt forgiveness granted by creditors in corporate reorganisation (‘haircuts’) should be reviewed. Under the current legislation, these haircuts may be treated as taxable income. As a result, financially distressed debtors may be required to pay taxes for certain income that did not involve any actual generation of cash flows. This article argues that, by implementing tax reforms, local and foreign companies will be able to maximise the benefits associated with having access to the efficient insolvency framework implemented in Singapore.